New species of Daidalotarsonemus and Excelsotarsonemus (Acari, Tarsonemidae) from the Brazilian rainforest - Rezende, Jose Marcos [UNESP]; Lofego, Antonio Carlos [UNESP]; Ochoa, Ronald; Bauchan, Gary (Pensoft Publ, 2015)
Three new species of Tarsonemidae, Daidalotarsonemus oliveirai Rezende, Lofego &Ochoa, sp. n., Excelsotarsonemus caravelis Rezende, Lofego &Ochoa, sp. n. and Excelsotarsonemus tupi Rezende, Lofego &Ochoa, sp. n. are described and illustrated. Measurements for these species are provided, as well as drawings, phase contrast (PC), differential interference contrast (DIC) and low temperature scanning electron microscopy (LT-SEM) micrographs. Some characters, which have not been used or clearly understood, are described herein. Biological, ecological and agricultural aspects about the role of these species in the rainforest and its surrounding environment are briefly discussed.
Keywords: Atlantic Forest; Canopy; Faunistics; LT-SEM; Systematics; Tarsonemoidea; Trombidiformes